Funkcja personalna w grupie kapitałowej - od centralizacji do decentralizacji - Jagoda, Agnieszka (Personnel function in capital group - from centralization to decentralization, 2006)
Regardless of the way of defining of the personnel function in the literature, its importance in the view of organizational aim realization is always stressed. There are no premises not to transfer this trend onto capital groups, although this is properly reflected neither in empirical studies nor in Polish and foreign literature. The main aim of this paper is to try to arrange certain changes in personel function organization and to transfer them to capital groups.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1141, s. 217-224